The determinants of cash holding level in UK’s companies – do the sales risks have significant impact? - TIian, Fangming (2013)
In this dissertation, cash holding level are analysed with 2004 - 2013 data from all firms in 13 industries from Bureau Van Dyke Fame database. The main hypothesis is that cash holding level should be positively related to the risk level. There are two dependent variables used for measuring cash holding level, cash to asset ratio and cash to sales ratio. Using cash sales ratio, the hypothesis is supported. There are mixed evidence of trade off, pecking order and agency theory in the results. Income smoothing practice and low level of cash distribution is implied by the results. There sales risk is also more sensitive with cash sales ratio compare to cash asset ratio.